Pertussis in the Voronezh Region: Epidemiology and Vaccination - N. P. Mamchik; N. V. Gabbasova; T. N. Sitnik; L. V. Steinke (Эпидемиология и вакцинопрофилактика)
Relevance. In recent years, the increase in the incidence of pertussis has been observed in many countries despite high vaccination coverage of the child population.Purpose: was to study the epidemiological features of whooping cough in the Voronezh region for the period from 2008 to 2018 years.Methods. The research material was data the annual form No. 2, 5, 6 of Rosstat for 2008 through 2018. Statistical data processing was performed using Microsoft Excel 2007.Results. The epidemiological features of pertussis in the Voronezh region for the period from 2008 to 2018 have been studied. Despite the high coverage of preventive vaccinations in children of the first years of life, in recent years, the incidence of pertussis increased the average Russian rates by 3,5 times. In the age structure of the diseased there was a tendency to increase the proportion of schoolchildren and adults. Analysis of the reports showed that half of the cases were vaccinated at the prescribed age, but the interval after vaccination before the illness was an average of 9 years.Conclusions. In recent years, there has been a tendency to an increase in the incidence of whooping cough in the Voronezh region. The incidence of vaccinated indicates the natural extinction of post-vaccination immunity to school age and requires a decision on the introduction of revaccination of schoolchildren with actual acellular vaccines.